Central Vestibular Functions Correlate With Fatigue and Walking Capacity in People With Multiple Sclerosis. Issue 9 (25th June 2021) - Cochrane, Graham D; Christy, Jennifer B; Motl, Robert W
Abstract: Objective: Imbalance and fatigue are among the most common and disabling symptoms of multiple sclerosis (MS). Vestibular rehabilitation studies demonstrate not only improvements in balance but fatigue also, suggesting a relationship between central vestibular integration and fatigue. The objective of this study was to determine whether the relationship between balance and fatigue in people with MS is seen between other measures of central vestibular integration and fatigue and to understand how central vestibular integration measures interrelate. Methods: This cross-sectional study consisted of 40 people with MS (age = 27–55 years, Expanded Disability Severity Scale score = 1.0–6.5) who completed vestibular ocular reflex testing, subjective visual vertical testing, static posturography, dynamic gait, 2 self-report fatigue surveys, and a 6-Minute Walk Test to assess walking capacity/physical fatigue was completed. Spearman correlations were calculated between variables. Results: Measures of central vestibular integration were significantly correlated with measures of fatigue and walking capacity and with each other. The correlations between physical fatigue and central vestibular functions were larger than self-reported fatigue correlations with central vestibular functions. Conclusion: The relationship between balance and fatigue extends to other measures requiring central vestibular integration, suggesting a deficit in central vestibular processing in people with MS. These measures may compliment balance assessment as outcome measures for vestibular rehabilitation in people with MS. Fatigue measures should be included in vestibular rehabilitation as secondary outcomes. Impact: Correlations between central vestibular integration and fatigue in people with MS suggest that future studies of vestibular rehabilitation should include fatigue, as a secondary outcome measure as vestibular function and fatigue may share similar a similar etiology in people with MS.